Coupling AFM and CLSM to investigate the effect of ageing on the bee structures of bitumen. (December 2021) - Pipintakos, Georgios; Blom, Johan; Soenen, Hilde; Van den bergh, Wim
Highlights: The effect of ageing on the bee structures of bitumen is explored via AFM and CLSM. Four waxy and two wax-free binders are investigated. The number of bees per μm 2 and bee area percentage decrease with ageing as confirmed by both techniques. The size of the bee structures increases upon ageing. Shape probabilistic values of the bee structures are extracted. Abstract: Bitumen's surface microstructure is in general well-documented and most recent theories postulate the effect of crystalline wax on the so-called bee structures. Although it is widely accepted that ageing has an effect on this unique microstructure yet conflicting literature exists on clear trends. This paper explores the effect of ageing on the bee structures of bitumen, employing two advanced microscopic techniques: an Atomic Force Microscopy (AFM) and a Confocal Laser Scanning Microscopy (CLSM). Four waxy and two wax-free bituminous binders are investigated before and after sequential laboratory short- and long-term ageing. The study demonstrates that the number of bees per μm 2 and bee area percentage decrease with ageing, whereas their size is increasing. A systematic analysis of the waveform characteristics is also provided for the peaks and valleys as well as the shape probabilistic values of the bee structures. In conclusion, the results of the two techniques are in good agreement, reporting similar trends upon ageing for the relative bee density. Differences are mainly identified in the waveform calculations. It is believed that this systematic investigation may assist in enhancing the understanding of the effect of ageing on the surface microstructure, the wax distribution as well as on the wax crystallisation.